Apigenin rich-Limonium duriusculum (de Girard) Kuntze promotes apoptosis in HCT116 cancer cells. Issue 17 (19th August 2021) - Hamadou, Meriem Hadjer; Kerkatou, Messaoud; Gatto, Pamela; Pancher, Michael; Bisio, Alessandra; Inga, Alberto; Menad, Ahmed; Benayache, Samir; Benayache, Fadila; Ameddah, Souad
Abstract: The pro-apoptotic property of n -BuOH extract of Limonium duriusculum (BEL) and its major isolated components [apigenin (APG1) and apigenin7-O-β-D-(6''-methylglucuronide) (APG2)] were tested. The anti-proliferative IC50 of BEL and APG1 was quantified as 7.60 µg/mL and 25.74 µM respectively, while APG2 did not affect cell proliferation in HCT116 p53 wild type cells. Growth inhibition by BEL treatment was associated with reduced signaling from the MAP kinase, activation of the p53 response pathway and PARP cleavage. The multi-effect of Limonium duriusculum could be due through their major apigenin compounds and the other bioactive constituents that may possibly act in synergy to exercise the most favorable anti-tumor activities. Abstract : UF0001